2022
DOI: 10.1038/s41531-022-00367-y
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiological evaluation of the LRRK2 G2385R risk variant for Parkinson’s disease

Abstract: Missense variants in leucine-rich repeat kinase 2 (LRRK2) lead to familial and sporadic Parkinson’s disease (PD). The pathological features of PD patients with LRRK2 variants differ. Here, we report an autopsy case harboring the LRRK2 G2385R, a risk variant for PD occurring mainly in Asian populations. The patient exhibited levodopa-responsive parkinsonism at the early stage and visual hallucinations at the advanced stage. The pathological study revealed diffuse Lewy bodies with neurofibrillary tangles, amyloi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…Mutant LRRK2-mediated Rab phosphorylation can cause endocytic defects (Liu et al, 2020; Rivero-Ríos et al, 2020; Streubel-Gallasch et al, 2021), and LRRK2-modified Rab10 localizes to and promotes secretion from stressed lysosomes (Eguchi et al, 2018; Kluss et al, 2022). Interestingly, phosphorylated Rab10 (pRab10) levels are elevated in the CNS of AD and PD patients, and pRab10 has been reported to co-localize with pathological tau (Yan et al, 2018; Tezuka et al, 2022) suggesting that post-translational modification of Rab10 modifies the disease state. Whether Rab10’s phosphorylation status affects its ability to regulate prion-like activity of mHTT ex1 or other amyloid aggregates warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Mutant LRRK2-mediated Rab phosphorylation can cause endocytic defects (Liu et al, 2020; Rivero-Ríos et al, 2020; Streubel-Gallasch et al, 2021), and LRRK2-modified Rab10 localizes to and promotes secretion from stressed lysosomes (Eguchi et al, 2018; Kluss et al, 2022). Interestingly, phosphorylated Rab10 (pRab10) levels are elevated in the CNS of AD and PD patients, and pRab10 has been reported to co-localize with pathological tau (Yan et al, 2018; Tezuka et al, 2022) suggesting that post-translational modification of Rab10 modifies the disease state. Whether Rab10’s phosphorylation status affects its ability to regulate prion-like activity of mHTT ex1 or other amyloid aggregates warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, this variant has been identified in approximately 5% of the population, a classification that aligns with ACMG’s BS1 (Strong benign criteria), and has also received a benign classification from in silico prediction tools (BP4). Nevertheless, the biochemical assessment of LRRK2 G2385R in postmortem brain samples from Parkinson’s disease patients has revealed heightened kinase activity and synucleinopathy as distinctive pathological features (19). Despite its classification as benign according to ACMG guidelines, the presence of this mutation in a significant number of sporadic PD cases suggests a narrative that diverges from its classification.…”
Section: Discussionmentioning
confidence: 99%
“…LRRK2 mutation is the most common etiology of familial PD. Notably, the G2385R variant is a common PD risk allele in Asian populations, and individuals, harboring this mutation exhibit elevated levels of LRRK2 kinase and pro‐inflammatory factors in the brain, in addition to displaying levodopa‐responsive Parkinson's syndrome at an early stage, Lewy body formation, neurofibrillary tangles, and mild neuroinflammation on histopathological examination (Tezuka et al, 2022). Similarly, It is reported that the G2019S mutation can increase LRRK2 kinase activity and aggravate neuronal death, while carriers of the G2019S mutation show elevated levels of peripheral pro‐inflammatory cytokines (Gardet et al, 2010).…”
Section: Introductionmentioning
confidence: 99%